2014
DOI: 10.1038/ncomms5464
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the micromechanisms behind semi-solid metal deformation with time-resolved X-ray tomography

Abstract: The behaviour of granular solid–liquid mixtures is key when deforming a wide range of materials from cornstarch slurries to soils, rock and magma flows. Here we demonstrate that treating semi-solid alloys as a granular fluid is critical to understanding flow behaviour and defect formation during casting. Using synchrotron X-ray tomography, we directly measure the discrete grain response during uniaxial compression. We show that the stress–strain response at 64–93% solid is due to the shear-induced dilation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 34 publications
(43 reference statements)
2
60
1
2
Order By: Relevance
“…Further, the composite subjected to 50% deformation show a higher amount of porosity compared to the 30% deformation. Similar observations of increase in porosity with increase in compressive deformation in semi-solid state in Al-Cu alloy was made by Kareh et al [37] in their insitu synchrotron XCT measurements. They found that semi-solid alloy with a solid fraction greater than 70% causes porosity formation and subsequently leads to cracking of the sample.…”
Section: Accepted M Manuscriptsupporting
confidence: 70%
“…Further, the composite subjected to 50% deformation show a higher amount of porosity compared to the 30% deformation. Similar observations of increase in porosity with increase in compressive deformation in semi-solid state in Al-Cu alloy was made by Kareh et al [37] in their insitu synchrotron XCT measurements. They found that semi-solid alloy with a solid fraction greater than 70% causes porosity formation and subsequently leads to cracking of the sample.…”
Section: Accepted M Manuscriptsupporting
confidence: 70%
“…This work also shows that liquid-filled fissures can open at 'very small' macroscopic shear strains of 1-5% because, at such high solid fraction, samples undergo a large degree of shearinduced dilation [31,32] as a result of the solid grains being so tightly packed. In the case of thin sample radiography where the sample has a large free surface area and no liquid reservoir, the decreasing liquid pressure due to inadequate or insufficient liquid flow to the expanding liquid-filled interstices causes the drawing-in of menisci from the sample surface in a cracklike manner.…”
Section: Implications For Continuous Castingmentioning
confidence: 65%
“…Note that the pushplate moves vertically upwards from the bottom right of each image. It can be seen that, as the pushplate intrudes into the sample, the space between the grains increases and fills with liquid, seen in lighter grey in Figure 2 The opening of spaces between the grains as the pushplate shears the sample is the phenomenon of shear-induced dilation or Reynold's dilatancy [27] which is widespread in particulate materials [28][29][30] and has been shown to occur in semi-solid alloys [13,31,32]. This is shown at higher magnification in Figure 3 The shear-induced dilation deformation mechanism can be understood from the group of four grains shown in Figure 4(a) (which is from the region highlighted in Figure 3 The lack of grain-grain cohesion indicates that most grains are separated by liquid films and not coalesced grain boundaries.…”
Section: Shear-induced Dilationmentioning
confidence: 99%
“…In recent years, synchrotron X-ray imaging has been extensively applied to the in situ study of solidification [2,11,12], fragmentation [8,13] and coarsening mechanisms [14], pore and bubble growth during solidification [15,16], and semi-solid processing [17][18][19]. Huang et al [20] recently reported measurement of the size distribution of cavitation gas bubbles in an AlCu alloy melt using the synchrotron X-ray radiography whilst the current authors used it to study the ultrasonic capillary effect in a molten metallic alloy [21].…”
Section: Introductionmentioning
confidence: 99%